2001
DOI: 10.1097/00005344-200110000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Enrasentan Improves Survival, Limits Left Ventricular Remodeling, and Preserves Myocardial Performance in Hypertensive Cardiac Hypertrophy and Dysfunction

Abstract: Evidence suggests that endothelin receptor antagonists may have therapeutic potential for the chronic treatment of heart failure. In the current study, the effects of an orally active mixed endothelin-A/endothelin-B (ETA /ETB ) receptor antagonist (enrasentan) were assessed in a model of cardiac hypertrophy and dysfunction (spontaneously hypertensive stroke prone rats) maintained on a high-salt/high-fat diet. Echocardiography was used to quantify cardiac performance and left ventricular dimensions. Enrasentan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Enrasentan, another nonselective ET-A/ET-B receptor-antagonist, was evaluated in a rat model of hypertensive cardiac hypertrophy and dysfunction [149]. Sixteen-week survival was significantly better than controls, and improvements in SV and CI, indices of LV mass, and circulating aldosterone were observed, again suggesting that combined ET-A/ ET-B receptor antagonism has the potential to attenuate ventricular remodeling in the experimental setting.…”
Section: Endothelin Receptor Antagonists In Experimental Heart Failurementioning
confidence: 99%
“…Enrasentan, another nonselective ET-A/ET-B receptor-antagonist, was evaluated in a rat model of hypertensive cardiac hypertrophy and dysfunction [149]. Sixteen-week survival was significantly better than controls, and improvements in SV and CI, indices of LV mass, and circulating aldosterone were observed, again suggesting that combined ET-A/ ET-B receptor antagonism has the potential to attenuate ventricular remodeling in the experimental setting.…”
Section: Endothelin Receptor Antagonists In Experimental Heart Failurementioning
confidence: 99%
“…Cosenzi et al have demonstrated that the drug normalizes blood pressure and protects target organs in rats with hypertension induced by a high fructose diet (14). In SHR-stroke prone rats with high-salt, high fat diet the reduction in blood pressure was not significant (68).…”
Section: Arterial Hypertensionmentioning
confidence: 99%
“…Enrasentan treated rats with cardiac hypertrophy and dysfunction induced by banding had higher stroke volume and cardiac index, improved survival, and reduced LV mass index, aldosterone, and pro-atrial natriuretic peptide concentrations. 7 The present study is the first to have compared an endothelin antagonist, enrasentan, directly with an ACE inhibitor, enalapril, in asymptomatic patients with LV dysfunction. The goal was to determine whether treatment with an endothelin receptor antagonist may have an early role in slowing the progression of HF.…”
mentioning
confidence: 93%